What is digital history? - Salmi, Hannu (Cambridge, UK ; Medford, PA : Polity, 2021)
"The first student handbook on digital methods and sources for historians"-- Provided by publisher.
Includes bibliographical references and index.
Keywords: History -- Computer network resources; History -- Methodology; History -- Research